A Foot to Last a Lifetime—Is Hindfoot Fusion Ever Appropriate for Pediatric Orthopaedic Conditions?. (July 2021) - Kelly, Derek M.
Abstract : Introduction: Hindfoot deformities in the pediatric population can be painful and result in severe limitations. Although arthrodesis is known to relieve pain, there are concerns over its use because of the risk that adjacent joint degenerative disease could result, leading to a new source of pain, dysfunction, and additional surgical procedures later in life. Methods: A literature review of hindfoot fusions in children focused on articles with the highest levels of evidence and those of particular historical significance. Case examples were obtained by querying the billing records of the local clinic system for Current Procedural Terminology (CPT) codes of hindfoot arthrodeses. Surgery procedures were performed by both fellowship-trained pediatric orthopaedists and fellowship-trained foot and ankle orthopaedic surgeons. Results: The medical literature for this topic generally is divided into 2 main types of articles: those that describe hindfoot fusion procedures for a specific type of deformity or disease process and those that provide the indications and results of a single type of arthrodesis. Long-term follow-up studies are limited. Discussion: The long-term risk of degeneration to adjacent joints has been studied, with mixed results. Other problems, such as recurrent deformity, overcorrection, pseudarthrosis, osteonecrosis, and foot shortening also may be encountered over intermediate-term follow-up. Nevertheless, in properly chosen patients, hindfoot fusion can offer a great improvement over the damaging and destructive deformities of the feet caused by a variety of diseases and traumatic injuries. Hindfoot fusions have been used for the treatment of foot deformities secondary to severe trauma, hemophilia, tarsal coalition, clubfoot, and neurological disease such as polio, static encephalopathy, hereditary motor and sensory neuropathies, and myelodysplasia. Conclusions: Hindfoot fusion in a child or adolescent should be considered only for the most extreme cases when all other options, short of amputation, have been considered or exhausted. While these procedures can offer improvement in the challenging cases, the surgeon should be aware of their long-term implications, including adjacent joint degeneration.